2019
DOI: 10.1111/1346-8138.14774
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood eosinophilia is associated with the presence of skin ulcers in patients with systemic sclerosis

Abstract: The role of eosinophil in systemic sclerosis (SSc) is still controversial. In the present study, the relationship between skin ulcers and peripheral blood eosinophilia were analyzed in patients with SSc. We retrospectively investigated the clinical records of all patients who were diagnosed with SSc on the basis of American College of Rheumatology/European League Against Rheumatism 2013 criteria, and were followed up for more than 2 years at Wakayama Medical University. As a result, maximum eosinophil counts d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(35 reference statements)
0
6
1
Order By: Relevance
“…Th2 cells support activation of eosinophils and B cells producing IgE immunoglobulins. In this respect it is of interest that SSc patients with skin ulcers showed significantly increased eosinophil counts compared with those without (20), and that eosinophils play an important role in the development of fibrosis in SSc (33,34). However, in the present series we did not find a correlation between eosinophil counts and presence of ulcers or IgE-anti-CENP-A/B reactivity which may be due to selection criteria or low number of patients.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Th2 cells support activation of eosinophils and B cells producing IgE immunoglobulins. In this respect it is of interest that SSc patients with skin ulcers showed significantly increased eosinophil counts compared with those without (20), and that eosinophils play an important role in the development of fibrosis in SSc (33,34). However, in the present series we did not find a correlation between eosinophil counts and presence of ulcers or IgE-anti-CENP-A/B reactivity which may be due to selection criteria or low number of patients.…”
Section: Discussioncontrasting
confidence: 63%
“…Since it had been reported that the presence of skin ulcers in SSc is correlated with blood eosinophilia (20) we also analysed IgE-anti-CENP-A/B reactivity in relation to eosinophil counts (Supplemental Table S2). However, there was no significant difference between patients with eosinophils >300/ mm 3 as compared to patients with eosinophil counts < 300/mm 3 (p=0.45 for IgE-anti-CENP-A and p=0.78 for IgE-anti-CENP-B), and there was also no significant correlation between absolute eosinophil counts and IgE-anti-CENP-A/B reactivity (r=0.09 and r=-0.07, respectively).…”
Section: Correlation Of Ige-autoantibodies In Ssc With Clinical Manif...mentioning
confidence: 99%
“…Furthermore, eosinophil counts were significantly correlated with severe interstitial lung disease (ILD) and an increased skin thickness in patients with SSc, but not in patients with other collagen diseases [ 32 ]. In addition, the presence of skin ulcers in SSc has been associated with elevated counts of peripheral blood eosinophils [ 33 ]. Collectively, these results implicate eosinophils in the pathogenesis of SSc including the hallmarks of inflammation and vascular dysfunction.…”
Section: The Role Of Immune Cells In Ssc-related Inflammation and Fib...mentioning
confidence: 99%
“…Also, recently, an international prospective study identified the mean number of capillaries per millimetre in the middle finger of the dominant hand, the number of DU at enrolment and the presence of critical digital ischaemia at enrolment as risk factors for the development of new DU in SSc patients 24 . Furthermore, peripheral blood eosinophilia is shown to be associated with the presence of DU in SSc patients 25 . Moreover, a new clinical score for SSc‐related DU is proposed.…”
Section: Skin Manifestations Of Sclerodermamentioning
confidence: 99%